Exterior of the Mahamandapa and Ardhamandapa - Temples of India Project Team (Jio Institute, 2024)
The mahamandapa (pillared hall) features lateral protrusions on either side providing asanapatta and kakshasana (elevated sitting area or seat backs), above which are five dwarf pillars. It is connected to the ardhamandapa (partially closed hall), which also has dwarf pillars. The mouldings of the mahamandapa and ardhamandapa differ from those of the sanctum.